The efficacy and safety of salvianolic acids on acute cerebral infarction treatment: A protocol for systematic review and meta analysis. Issue 23 (5th June 2020) - Xin, Meiying; Hao, Yulei; Huang, Ge; Wang, Xu; Liang, Zhen; Miao, Jing; Ma, Di; Feng, Jiachun
Abstract: Background: Salvianolic acids (SA) has been widely used for the treatment of acute cerebral infarction (ACI) combined with basic western medicine therapy in China. This study was aimed to evaluate the efficacy and safety of SA on ACI treatment and its influence on neurological functions, activity of daily living, and cognitive functions. Methods: We retrieved related articles from PubMed, the Cochrane Center Controlled Trials Register, EMBASE, Medline, Ovid, Chinese National Knowledge Infrastructure, Chinese Biomedical Literature Database, and Wanfang Database without date and language restrictions. Finally, 58 randomized controlled trials were included from 239 retrieved records. Two researchers extracted the basic information and data from included articles and assessed the quality and analysis of data by using Review Manager 5.3. Results: The administration of SA significantly increased the total clinical effective rate of ACI treatment ( P  < .001) and improved the National Institute of Health Stroke Scale scores, modified Rankin Scale scores, and Barthel Index scores after treatment and 3 months after ACI ( P  < .05). The activities of daily living scores in the SA group were significantly increased after treatment ( P  < .001), whereas they were remarkably decreased 3 months after ACI ( P  < .001) compared with that in the control group. Besides, SA profoundly promoted the recovery of Montreal Cognitive Assessment scores ( P  < .001). However, the use of SA increased the risk of adverse events occurrence ( P  = .007). Conclusion: SA combined with basic western medicine treatment could promote neurological functions, daily living activities, and cognitive functions recovery of ACI patients. Although SA increased the risk of adverse events occurrence, these adverse events were easily controlled or disappeared spontaneously. Abstract : Supplemental Digital Content is available in the text